Short-term effects of lunch on children's executive cognitive functioning: The randomized crossover Cognition Intervention Study Dortmund PLUS (CogniDo PLUS) - Schröder, Maike; Müller, Katrin; Falkenstein, Michael; Stehle, Peter; Kersting, Mathilde; Libuda, Lars (Physiology & Behavior)

Mittagessen in der Schule – macht es die Kinder schlau oder müde? - Libuda, Lars; Schröder, M.; Müller, K.; Kersting, M. (Pädiatrische Praxis)

Fish and rapeseed oil consumption in infants and mothers: dietary habits and determinants in a nationwide sample in Germany - Stimming, Madlen; Mesch, Christina M.; Kersting, Mathilde; Libuda, Lars (European Journal of Nutrition)

Vitamin E Content and Estimated Need in German Infant and Follow-On Formulas With and Without Long-Chain Polyunsaturated Fatty Acids (LC-PUFA) Enrichment - Stimming, Madlen; Mesch, Christina M.; Kersting, Mathilde; Kalhoff, Hermann; Demmelmair, Hans; Koletzko, Berthold; Schmidt, Anne; Böhm, Volker; Libuda, Lars (Journal of Agricultural and Food Chemistry)

Dietary Lipid Intake only Partially Influences Variance in Serum Phospholipid Fatty Acid Composition in Adolescents: Impact of Other Dietary Factors - Vyncke, Krishna; Huybrechts, Inge; Van Winckel, Myriam; Cuenca Garcia, Magdalena; Labayen, Idoia; Gottrand, Frederic; Widhalm, Kurt; Leclercq, Catherine; Libuda, Lars; Manios, Yannis; Sjostrom, Michael; Molnar, Denes; et al. (Lipids)

Associations between macronutrient intake and serum lipid profile depend on body fat in European adolescents: the Healthy Lifestyle in Europe by Nutrition in Adolescence (HELENA) study - Bel-Serrat, Silvia; Mouratidou, Theodora; Huybrechts, Inge; Labayen, Idoia; Cuenca-García, Magdalena; Palacios, Gonzalo; Breidenassel, Christina; Molnár, Dénes; Roccaldo, Romana; Widhalm, Kurt; Gottrand, Frederic; Kafatos, Anthony; et al. (British Journal of Nutrition)
The present study aimed to investigate the relationships between macronutrient intake and serum lipid profile in adolescents from eight European cities participating in the HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) cross-sectional study (2006–7), and to assess the role of body fat-related variables in these associations. Weight, height, waist circumference, skinfold thicknesses, total cholesterol, HDL-cholesterol (HDL-C), LDL-cholesterol, TAG, apoB and apoA1 were measured in 454 adolescents (44 % boys) aged 12·5–17·5 years. Macronutrient intake (g/4180 kJ per d (1000 kcal per d)) was assessed using two non-consecutive 24 h dietary recalls. Associations were evaluated by multi-level analysis and adjusted for sex, age, maternal education, centre, sum of four skinfolds, moderate-to-vigorous physical activity, sedentary behaviours and diet quality index for adolescents. Carbohydrate intake was inversely associated with HDL-C (β = − 0·189, P < 0·001). An inverse association was found between fat intake and TAG (β = − 0·319, P < 0·001). Associations between macronutrient intake and serum lipids varied according to adiposity levels, i.e. an inverse association between carbohydrate intake and HDL-C was only observed in those adolescents with a higher waist:height ratio. As serum lipids and excess body fat are the major markers of CVD, these findings should be considered when developing strategies to prevent the risk of CVD among adolescents.

Food variety in commercial and homemade complementary meals for infants in Germany. Market survey and dietary practice - Mesch, Christina M.; Stimming, Madlen; Foterek, Kristina; Hilbig, Annett; Alexy, Ute; Kersting, Mathilde; Libuda, Lars (Appetite)

Time trends in dietary fat intake in a sample of German children and adolescents between 2000 and 2010: not quantity, but quality is the issue - Libuda, Lars; Alexy, Ute; Kersting, Mathilde (British Journal of Nutrition)
Dietary fat intake in childhood may influence the risk for developing chronic diseases. The objective of the present study was to examine secular trends in the parameters of fat intake between 2000 and 2010 in a sample of German children and adolescents ( n 808) participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) Study. Dietary data from 4380 3 d weighed dietary records were analysed using repeated-measures regression to determine time trends in fat quantity, i.e. the intake of total fat, and in fat quality, i.e. the ratios of SFA, MUFA and PUFA. In young children (2–3 years) and in adolescents (13–18 years), total fat intake remained stable over time, but decreased by 0·08 % of total energy (%E) per year in 4–12-year-old children. In 2010, median fat intake was at the upper end of the recommendations. SFA intake decreased slightly in 2–3- and 4–12-year-old children by 0·09 and 0·05 %E per year, respectively. MUFA and PUFA intakes remained stable in all the age groups except in adolescents. Here, PUFA intake decreased initially, but increased between 2005 and 2010. In 2010, only between 3 and 18 % of the respective age groups had an intake of SFA or PUFA within the recommendations. In conclusion, fat quantity and quality did not change substantially between 2000 and 2010. Fat quality, in particular, needs to be improved, since a large percentage of our sample did not meet the recommended intakes for SFA and PUFA.

Frequencies and demographic determinants of breastfeeding and DHA supplementation in a nationwide sample of mothers in Germany - Libuda, Lars; Stimming, Madlen; Mesch, Christina; Warschburger, Petra; Kalhoff, Hermann; Koletzko, Berthold Viktor; Kersting, Mathilde (European Journal of Nutrition)

Lunch at school, at home or elsewhere. Where do adolescents usually get it and what do they eat? Results of the HELENA Study - Müller, Katrin; Libuda, Lars; Diethelm, Katharina; Huybrechts, Inge; Moreno, Luis A.; Manios, Yannis; Mistura, Lorenza; Dallongeville, Jean; Kafatos, Anthony; González-Gross, Marcela; Cuenca-García, Magdalena; Sjöström, Michael; et al. (Appetite)

Effects of lunch on children’s short-term cognitive functioning: a randomized crossover study - Müller, K; Libuda, Lars; Gawehn, N; Drossard, C; Bolzenius, K; Kunz, C; Kersting, M (European Journal of Clinical Nutrition)

A Review of the Effects of Lunch: On Adults’ Short-term Cognitive Functioning - Müller, Katrin; Libuda, Lars; Terschlüsen, Anna Maria; Kersting, Mathilde (Canadian Journal of Dietetic Practice and Research)
Because of widespread irregular lunch consumption by both children and adults, information on the effects of lunch on short-term cognitive functioning is relevant to public health. In September 2012, a MEDLINE search was conducted for studies in which the effects of lunch on cognitive performance were examined. Eleven experimental studies published from 1981 to 1996 were found and evaluated; all involved adults. In three studies, the effects of lunch and lunch skipping were compared; the remaining studies involved a determination of the effects of lunch size and lunch composition. Results of studies in which lunch was compared with no lunch indicate that lunch leads to potential impairment of some aspects of cognitive functioning in the early afternoon. Lunch size may influence cognitive functioning, with impairment more likely to occur after a large lunch than a small lunch. Furthermore, in comparison with low-fat lunches, high-fat lunches seem to result in slower but more accurate responses to some cognitive tasks. However, these suggestions must be viewed with caution, as they are based on only a few studies and are not thoroughly supported by high-quality evidence. In addition, results obtained with adults are not applicable to children. Thus, the potential effects of lunch need further examination in children and adults.

Rekrutierung von Müttern mit Säuglingen in einer Interventionsstudie – erste Erkenntnisse aus der PINGU-Studie. - Mesch, C.; Stimming, M.; Wagner, A.; Libuda, Lars; Kersting, M. (Ernährungsumschau International)

Long term higher urinary calcium excretion within the normal physiologic range predicts impaired bone status of the proximal radius in healthy children with higher potential renal acid load - Shi, Lijie; Libuda, Lars; Schönau, Eckhard; Frassetto, Lynda; Remer, Thomas (Bone)

Dietary fatty acid intake, its food sources and determinants in European adolescents: the HELENA (Healthy Lifestyle in Europe by Nutrition in Adolescence) Study. - Vyncke, KE; Libuda, Lars; De Vriendt, T; Moreno, LA; Van Winckel, M; Manios, Y; Gottrand, F; Molnar, D; Vanaelst, B; Sjöström, M; González-Gross, M; Censi, L; et al. (Br J Nutr)

Beverage consumption among European adolescents in the HELENA study. - Duffey, KJ; Huybrechts, I; Mouratidou, T; Libuda, Lars; Kersting, M; De Vriendt, T; Gottrand, F; Widhalm, K; Dallongeville, J; Hallström, L; González-Gross, M; De Henauw, S; et al. (Eur J Clin Nutr)

Der Verzehr von Kochsalz und die Entwicklung des Körpergewichts. - Libuda, Lars; Alexey, Ute (Pädiatrische Praxis)

Consumption of dietary salt measured by urinary sodium excretion and its association with body weight status in healthy children and adolescents - Libuda, Lars; Kersting, Mathilde; Alexy, Ute (Public Health Nutrition)
Abstract Objective Highly processed foods such as convenience foods usually have a high salt content and therefore might indirectly act as adipogenic due to an increasing consumption of sugar-containing beverages (SCB). We examined the association between dietary salt and body weight status. Design We used data on urinary Na excretion as an indicator of dietary salt and BMI standard deviation score (BMI-SDS) and percentage body fat (%BF) of children and adolescents participating in the DONALD (Dortmund Nutritional and Anthropometric Longitudinally Designed) Study. Setting Dortmund, Germany. Subjects Children and adolescents ( n 364) who had at least two 24 h urine samples and two dietary records in the observational period between 2003 and 2009 were considered in our data analysis. Results Repeated-measures regression models revealed that urinary Na was positively associated with BMI-SDS (+0·202 SDS/g Na excretion at baseline; P < 0·001) and %BF (+1·303 %BF/g Na excretion at baseline; P < 0·01) at baseline in boys and girls. These associations remained significant after adjustment for SCB consumption and total energy intake. Furthermore, there was a positive trend between baseline Na excretion and the individual change in %BF in the study period (+0·364 increase in %BF/g Na excretion at baseline), which was confirmed after inclusion of SCB consumption or total energy intake. There was no significant association between the change in Na excretion and the concurrent change of either BMI-SDS or %BF in any model. Conclusions Our results suggest that a high intake of processed salty foods could have a negative impact on body weight status in children and adolescents independently from their consumption of SCB.

24h-Sodium excretion and hydration status in children and adolescents - Results of the DONALD Study - Alexy, Ute; Cheng, Guo; Libuda, Lars; Hilbig, Annett; Kersting, Mathilde (Clinical Nutrition)

Ansätze der Übergewichtsprävention durch verbessertes Trinkverhalten im Setting Grundschule - Muckelbauer, R.; Libuda, Lars; Clausen, K.; Kersting, M. (Bundesgesundheitsblatt - Gesundheitsforschung - Gesundheitsschutz)

Fluids and children’s health. - Muckelbauer, R.; Libuda, Lars; Kersting, M. (Developing Children´s Food Products.)

Convenience foods in children's diet and association with dietary quality and body weight status - Alexy, U; Libuda, Lars; Mersmann, S; Kersting, M (European Journal of Clinical Nutrition)

Comparison of the effects of dietary protein, androstenediol and forearm muscle area on radial bone variables in healthy prepubertal children - Libuda, Lars; Wudy, Stefan A.; Schoenau, Eckhard; Remer, Thomas (British Journal of Nutrition)
Adequate dietary habits are supposed to be one of the most important modifiable factors in osteoporosis prevention. However, the importance of specific nutrients is controversial. We examined relevant nutrients which are supposed to have an impact on bone parameters and compared their effect sizes with those of two known predictors of bone development: bone-related muscle mass and androgen levels. We analysed nutritional, hormonal and anthropometric data from 107 prepubertal children participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed Study. Diaphyseal bone mineral content (BMC), cortical area (CA), periosteal circumference, strength strain index and muscle area of the non-dominant forearm were measured by peripheral quantitative computed tomography. Data on long-term nutrient intakes (e.g. protein, Ca and vitamin D) were derived from 3 d weighed dietary records. Twenty-four hour urinary excretion rates of androgen metabolites including the sex steroid androstenediol were measured using GC–MS. Of all considered nutrients, only protein showed a trend for an association with BMC (β = +0·11; P = 0·073) and CA (β = +0·11; P = 0·056) in stepwise linear regression models. None of the other considered dietary variables was associated with bone parameters. The size of the bone anabolic effect of protein was partly comparable with that of androstenediol. Even though boys gained more bone mass in comparison with girls, the protein effect did not differ between sexes. Bone-related muscle area and sex steroids have the strongest effects on prepubertal diaphyseal bone. However, dietary protein may have a similar bone anabolic influence compared with androstenediol. In children without explicit nutrient deficits, protein seems to be the most important dietary component for diaphyseal bone status.

Urinary fructose: a potential biomarker for dietary fructose intake in children - Johner, S A; Libuda, Lars; Shi, L; Retzlaff, A; Joslowski, G; Remer, T (European Journal of Clinical Nutrition)

Longitudinal Associations between Endogenous Melatonin Production and Reported Sleep Duration from Childhood to Early Adulthood - Diethelm, Katharina; Libuda, Lars; Bolzenius, Katja; Griefahn, Barbara; Buyken, Anette; Remer, Thomas (Hormone Research in Paediatrics)

Bone-anabolic impact of dietary high protein intake compared with effects of low potential renal acid load, endogenous steroid hormones, and muscularity in children. - Remer, T.; Libuda, Lars (Nutritional Influences on Bone Health.)

Immigrational Background Affects the Effectiveness of a School-based Overweight Prevention Program Promoting Water Consumption - Muckelbauer, Rebecca; Libuda, Lars; Clausen, Kerstin; Toschke, André M.; Reinehr, Thomas; Kersting, Mathilde (Obesity)

Relation of Dietary Glycemic Index, Glycemic Load, and Fiber and Whole-Grain Intakes During Puberty to the Concurrent Development of Percent Body Fat and Body Mass Index - Cheng, G.; Karaolis-Danckert, N.; Libuda, Lars; Bolzenius, K.; Remer, T.; Buyken, Anette E. (American Journal of Epidemiology)

Long-term process evaluation of a school-based programme for overweight prevention - Muckelbauer, R.; Libuda, Lars; Clausen, K.; Kersting, M. (Child: Care, Health and Development)

A Simple Dietary Intervention in the School Setting Decreased Incidence of Overweight in Children - Muckelbauer, Rebecca; Libuda, Lars; Clausen, Kerstin; Reinehr, Thomas; Kersting, Mathilde (Obesity Facts)

Promotion and Provision of Drinking Water in Schools for Overweight Prevention: Randomized, Controlled Cluster Trial - Muckelbauer, R.; Libuda, Lars; Clausen, K.; Toschke, A. M.; Reinehr, T.; Kersting, M. (PEDIATRICS)

Soft drinks and body weight development in childhood: is there a relationship? - Libuda, Lars; Kersting, Mathilde (Current Opinion in Clinical Nutrition and Metabolic Care)

Getränkeverzehr und Übergewicht bei Kindern - Libuda, Lars; Muckelbauer, R.; Kersting, M. (Journal für Ernährungsmedizin)

Einfluss des Konsums von Erfrischungsgetränken auf den Ernährungs- und Gesundheits¬status von Kindern - Libuda, Lars (Ernährungsumschau)

DONALD News: Zusammenhang zwischen dem Verzehr von Erfrischungsgetränken und dem Knochenstatus von Kindern und Jugendlichen. - Libuda, Lars; Remer, Thomas; Kersting, M. (Ernährungsumschau)

Association between long-term consumption of soft drinks and variables of bone modeling and remodeling in a sample of healthy German children and adolescents - Libuda, Lars; Alexy, Ute; Remer, Thomas; Stehle, Peter; Schoenau, Eckhard; Kersting, Mathilde (The American Journal of Clinical Nutrition)

Konsum von Erfrischungsgetränken und Entwicklung des Körpergewichts im Kindes- und Jugendalter – Gibt es eine Verbindung? - Libuda, Lars; Alexey, U.; Stehle, P.; Kersting, M. (Aktuelle Ernährungsmedizin)

DONALD News: Erfrischungsgetränke und Ernährungsqualität. - Libuda, Lars; Kersting, M. (Ernährungsumschau)

Pattern of beverage consumption and long-term association with body-weight status in German adolescents – results from the DONALD study - Libuda, Lars; Alexy, Ute; Sichert-Hellert, Wolfgang; Stehle, Peter; Karaolis-Danckert, Nadina; Buyken, Anette; Kersting, Mathilde (British Journal of Nutrition)
In the present study the relationship between the consumption of different beverage groups and body-weight status in 5 years of study participation in German adolescents was investigated. We used anthropometric and dietary data from 3 d weighed records of 244 subjects between 9 and 18 years of age participating in the Dortmund Nutritional and Anthropometric Longitudinally Designed (DONALD) study. Only subjects with at least four out of six possible weighed dietary records were considered. A repeated-measures regression model (PROC MIXED) was used to analyse the effect of beverage consumption on body-weight status. BMI standard deviation scores (BMI-SDS) and body fat percentage (%BF) were chosen as the dependent variables. In boys, energetic beverage consumption was not associated with BMI-SDS or %BF, neither cross-sectionally nor prospectively. In girls, baseline consumption of energetic beverages did not predict baseline BMI-SDS, baseline %BF, or change in either variable over the study period. However, an increase in energetic beverage consumption over the study period was associated with an increase in BMI-SDS (+0.070 SDS/MJ increase in energetic beverage consumption; P = 0·01). Separate consideration of regular soft drinks and fruit juices revealed that, in girls, BMI-SDS increased with increased fruit juice consumption (+0·096 SDS/MJ increase in fruit juice consumption; P = 0·01), and to a lesser extent with regular soft drink consumption (+0·055 SDS/MJ increase in regular soft drink consumption; P = 0·08). In conclusion, these results suggest that an increase in energetic beverage consumption may result in weight gain, at least in adolescent girls.

DONALD News: Zuckerhaltige Getränke und Übergewicht bei Kindern. - Libuda, Lars; Alexey, U. (Monatsschriften Kinderheilkunde)